PepT1-targeted nanodrug based on co-assembly of anti-inflammatory peptide and immunosuppressant for combined treatment of acute and chronic DSS-induced ColitiS - Zhang, Daifang; Jiang, Longqi; Yu, Fengxu; Yan, Pijun; Liu, Yong; Wu, Ya; Yang, Xi (Frontiers in Pharmacology, 2024)
Colitis, as a chronic and recurrent inflammatory bowel diseases with limited therapeutic outcomes, is characterized by immune disorders and intestinal barrier dysfunction. Herein, we aim to develop KPV-FK506 nanoparticles (NPs) based on the co-assembly of an anti-inflammatory peptide (Lysine-pro-valine, KPV) and an immunosuppressant (FK506) for the combined treatment of colitis by regulating immune and intestinal barrier disorders. Notably, KPV can possess targeting ability for oligopeptide transporter 1 (PepT1) overexpressed in colonic epithelial and macrophages during colitis. In our study, we found NPs could be efficiently internalized by Caco-2 and RAW264.7 cells as well, localized to the inflamed colon preferentially. After administering with NPs, mice with DSS-induced acute or chronic colitis exhibited significant improvement in body weight, colon length, and disease activity index, which exposed that NPs could ameliorate murine colitis effectively. Moreover, treatment with NPs decreased levels of MPO, NO, ROS, and suppressed the inflammatory cytokines including tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6), which performed similarly to the healthy group. Furthermore, the treatment led to a notable reduction of the expressions of CD68 and CD3, which represented reduced infiltration of macrophages and T-lymphocytes. Additionally, the expression levels of tight junction proteins Claudin-5, Occludin-1, and ZO-1 were significantly diminished in the DSS group but were substantially restored in the NPs group, surpassing those observed in the KPV and FK506 groups. Our findings indicated that NPs can reduce inflammation and enhance epithelial barrier integrity by decreasing the infiltration of macrophages and T-lymphocytes. Collectively, those results demonstrated the effectively therapeutic outcome after using NPs in both acute and chronic colitis, suggesting that NPs can be as a potential therapeutic candidate for colitis.